Elmer Holmes Davis papers - Davis, Elmer Holmes, 1890-1958.; Davis, Elmer Holmes, 1890-1958.
Correspondence, speeches, lectures, writings, articles, radio scripts, subject file, government publications, press releases, biographical material, photographs, and other papers pertaining primarily to Davis's career in journalism and his service as director of the U.S. Office of War Information during World War II. Subjects include politics, literary affairs, and world events. Includes radio scripts of Davis's broadcasts for the Columbia Broadcasting System, inc., and the American Broadcasting Company; a typescript of Davis's book titled But We Were Born Free (1954); and letters from Chicago Tribune reporter Carolyn A. Wilson with her observations on conditions in France during World War I. Correspondents include Bernard Augustine De Voto, Edward R. Murrow, Harold Wallace Ross, James Thurber, Harry S. Truman, Hendrik Willem Van Loon, Sumner Welles, and William Allen White.
Author, journalist, news analyst, and government official.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: De Voto, Bernard Augustine, -- 1897-1955 -- Correspondence; Murrow, Edward R. -- Correspondence; Ross, Harold Wallace, -- 1892-1951 -- Correspondence; Thurber, James, -- 1894-1961 -- Correspondence; Truman, Harry S., -- 1884-1972 -- Correspondence; Van Loon, Hendrik Willem, -- 1882-1944 -- Correspondence; Welles, Sumner, -- 1892-1961 -- Correspondence; White, William Allen, -- 1868-1944 -- Correspondence; Wilson, Carolyn A., -- -1960 -- Correspondence; United States. -- Office of War Information; American Broadcasting Company; Columbia Broadcasting System, inc; Journalism; Literature -- 20th century; World politics; World War, 1914-1918 -- France; World War, 1939-1945 -- Propaganda; United States -- Politics and government -- 20th century; Authors; Journalists; News analysts; Public officials